The Photon is Naked: The Role of Textbook in the Building of a Common World (Revista Brasileira de Pesquisa em Educação em Ciências, 2024)
Given the ontological plurality associated with Quantum Theory (i.e., the multiplicity of interpretations of the theory), we investigated the approaches of 22 undergraduate textbooks in the process of composing a possible common world about electromagnetic radiation. In the work, we align ourselves, on the one hand, with the proposals of Eduardo Viveiros de Castro, Bruno Latour and Isabelle Stengers, arguing that reality occurs through a cosmopolitical process in which non-transcendental multinatures negotiate to achieve common stabilization. These perspectives collide with a central metaphysics of modernism: a reality grounded in a unique and innate nature (called cosmopolitan). On the other hand, we started from Bakhtin’s Philosophy of Language to analyze the style of speech cited in the books. The main analysis of the text is to identify whether the books are cosmopolitan or cosmopolitical, and whether the boundaries of the cited discourse are explicit or erased. The results found in our analysis indicate that there is no ontologically stabilized electromagnetic radiation proposition when we consider all textbooks. However, as most of these same books hide the limits between propositions, it is evident that the authors simulate that there is a consensus in the scientific community regarding their ontology.